Numerical Investigation of Jet Control Using Two Pulsed Jets under Different Amplitudes - Qitai Eri; Wenhao Ding; Bo Kong (Energies, 2022)
A turbulent jet with a Reynolds number of 71,000, controlled by a pair of pulsed jets operating 180° out of phase, is investigated by large-eddy simulation. The effect of the forcing amplitude on jet development and generated coherent structures is investigated through six cases: an unforced case and five cases at different amplitudes. With this forcing mode, the jet bifurcates in the far field that promotes the spread of the shear layer. It was found that the jet yields the largest bifurcation angle at medium amplitude, while the bifurcation is restrained at lower or higher amplitudes. As the amplitude increases, the streamwise vortex pair generated by the control jet is stronger and penetrates deeper into primary jet. This phenomenon reduces the inclination of vortex ring when mutual interaction between vortex ring and streamwise vortex pair occurs. Meanwhile, at higher amplitudes, the inclined vortex ring is stronger and unevenly distributed, prompting the jet bifurcation. In order to investigate the coupling effect of amplitude and frequency, different forcing frequencies were also simulated. The results demonstrated that the optimal frequency based on centerline velocity decay rate decreases with increasing amplitude; however, it eventually saturates around StD = 0.1.